Bladder function and falls in individuals with multiple sclerosis. Issue 22 (22nd October 2016) - Sung, JongHun; Shen, Sa; Motl, Robert W.; Sosnoff, Jacob J.
Abstract: Purpose: To examine the association between bladder function and falls while controlling for mobility in individuals with multiple sclerosis (MS). Methods: A total of 92 ambulatory individuals with MS (mean age ± SD = 59.1 ± 7.3 years, female n  =   69) were divided into two groups based on self-reported bladder function (none-mild n  =   43 versus moderate-severe n  =   49). The main outcome measure was a number of self-reported falls in the previous 3 months. Participants' demographic information (age, type of MS, gender, use of the assistive device) was also collected. The balance was quantified with the Berg balance scale, and walking speed was indexed with the timed 25-foot walk test. Negative binomial regression analysis was used to examine the association between bladder function and falls in individuals with MS while controlling for balance and walking. Results: The median number of self-reported falls in the previous 3 months was 2 (interquartile range, 0–4). The severe bladder dysfunction group was more likely (incidence rate ratio = 1.84) to have a greater number of self-reported falls compared to mild bladder dysfunction group when balance and walking were taken into account. Conclusion: Bladder dysfunction is related to falls history independently of mobility in individuals with MS. Future research examining whether bladder management programmes have an impact on fall incidence in MS is warranted. Implications for rehabilitation: Bladder dysfunction and falls are common health concerns in individuals with multiple sclerosis. Bladder dysfunction was associated with the number of falls in individuals with MS, and this association was independent of mobility. Bladder management should be included in fall prevention strategies in individuals with MS.